The Structural Basis of Long-Term Potentiation in Hippocampal Synapses, Revealed by Electron Microscopy Imaging of Lanthanum-Induced Synaptic Vesicle Recycling - Heuser, John E. (Frontiers in Cellular Neuroscience, 2022)
Hippocampal neurons in dissociated cell cultures were exposed to the trivalent cation lanthanum for short periods (15–30 min) and prepared for electron microscopy (EM), to evaluate the stimulatory effects of this cation on synaptic ultrastructure. Not only were characteristic ultrastructural changes of exaggerated synaptic vesicle turnover seen within the presynapses of these cultures—including synaptic vesicle depletion and proliferation of vesicle-recycling structures—but the overall architecture of a large proportion of the synapses in the cultures was dramatically altered, due to large postsynaptic “bulges” or herniations into the presynapses. Moreover, in most cases, these postsynaptic herniations or protrusions produced by lanthanum were seen by EM to distort or break or “perforate” the so-called postsynaptic densities (PSDs) that harbor receptors and recognition molecules essential for synaptic function. These dramatic EM observations lead us to postulate that such PSD breakages or “perforations” could very possibly create essential substrates or “tags” for synaptic growth, simply by creating fragmented free edges around the PSDs, into which new receptors and recognition molecules could be recruited more easily, and thus, they could represent the physical substrate for the important synaptic growth process known as “long-term potentiation” (LTP). All of this was created simply in hippocampal dissociated cell cultures, and simply by pushing synaptic vesicle recycling way beyond its normal limits with the trivalent cation lanthanum, but we argued in this report that such fundamental changes in synaptic architecture—given that they can occur at all—could also occur at the extremes of normal neuronal activity, which are presumed to lead to learning and memory.